Research on Deterioration Model of Concrete Road in Cold Area. Issue 3 (March 2020) - Jin, Cheng; Zhang, Yiduo
Abstract: Based on the concrete damage data under the interaction of fatigue loads and freeze-thaw cycles, a concrete freeze-thaw cycle deterioration model and a fatigue damage deterioration model are established respectively. Based on the concrete fatigue damage deterioration model, a freeze-thaw influence factor is introduced, and a freeze-thaw The model of concrete degradation under fatigue and fatigue, and the relationship between freeze-thaw damage, fatigue damage and time are discussed separately, so as to study the remaining life of concrete roads.